IMPLEMENTATION OF LOCAL CULTURAL ACTIVITY THROUGH LEARNING SOCIAL SCIENCE (IPS) IN ELEMENTARY SCHOOL STUDENTS OF SURAKARTA - Oktiana Handini; Bambang Hermoyo (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The values of local cultural wisdom in order to remain a fundamental force of national culture are through learning Social Sciences (IPS) for students in Elementary Schools (SD), as learning materials have a significant role in developing the characteristics of local cultural wisdom for students.The purpose of this study was to explore and find the implementation of local cultural wisdom through social science learning (IPS) for Elementary School students in Surakarta.Ethnographic research methods with qualitative descriptive analysis in terms of historical, sociological, and pedagogical perspectives. The data were obtained through surveys, observations and interviews with principals, teachers, and elementary school students in the city of Surakarta, using proportional sampling techniques.The results showed that the implementation of local cultural wisdom through social science learning (IPS) for Elementary School students in Surakarta was 261 state and private elementary schools (five districts). An understanding of the value of local cultural wisdom that has high cultural historical value and pedagogical value can support the content of social science learning in implementing local cultural wisdom in Surakarta. Social studies learning originates from the history of the city of Surakarta, the characteristics and life of its people, the culture of mutual cooperation, courtesy and respect for others as well as regional cultural arts that are included in the local content curriculum in the form of Javanese songs, and geguritan can be applied in social studies learning. Thus, these local cultural values can be used as a source of social studies learning, with the aim of making social studies learning more meaningful for students in shaping their character. Keywords: Local Cultural Wisdom, Social Sciences (IPS),